The Influence of the MURDER Learning Model on High School Students' Mathematical Concept Understanding and Mood - Rahmawati; Kadir; Masi, La; Salim (Jurnal Amal Pendidikan, 2024)
This study aims to examine the differences in the improvement of mathematical concept understanding and mood enhancement between students taught using the MURDER learning model and those taught using the direct learning model. This type of research is a quasi-experiment with a pretest-posttest control group design. The population of this study consists of all the students in grade XI, totaling 275 students. The sample was taken using purposive sampling technique. From this method, two classes were selected as the sample. The research instruments included a test of students' mathematical concept comprehension, a student mood questionnaire, and a teacher observation sheet. The data analysis techniques used were descriptive and inferential analysis. The results of the study indicate that: (1) The description of students' mathematical concept comprehension ability, taught using the MURDER learning model and the direct instruction model, showed average N-Gain values of 0,3634 and 0,2827, respectively. (2) The description of student mood, taught using the MURDER learning model and the direct instruction model, showed average N-Gain values of 0,5709 and 0,4291, respectively. (3) Based on the results of the MANOVA test, the F value has a significance level of 0,009 < a = 0,05 so H0 is rejected. So, it can be concluded that there is a difference in the improvement of mathematical concept understanding and mood enhancement between students taught using the MURDER learning model and those taught using the direct instruction model